HAK DAN KEWAJIBAN INGKAR NOTARIS DITINJAU DARI UNDANG-UNDANG NO. 2 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NO.30 TAHUN 2004 TENTANG JABATAN NOTARIS DAN PANDANGAN HUKUM ISLAM - NOVITA MERY (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Prof. H.M. Hasballah Thaib, MA, PhD3. Notaris Dr. Suprayitno, SH, MKn Right and obligation of objection is stipulated in UUJN (Notarial Act No. 2/2014 on the amendment of UUJN No. 30/2004 for a Notary in doing his job as a public official in keeping confidentiality of the deeds he has made and the privacy of the persons appearing. Aricle 4, Article 16, paragraph 1, letter f, Article 54, and Article 66 of UUJN are legal ground for the implementation of the right and obligation of objection.The research used juridical normative method which was aimed to analyze legal provisions such as UUJN No. 30/2004 which was amended to UUJN No. 2/2014. It also used descriptive analytic approach by giving argumentation from the research result. The results of the discussion of the problems that arise in this study are that legal arrangements regarding the rights and obligations of notaries to deny are contained in paragraph Aricle 4, (1) (f) of Article 16, paragraphs (1), (2), (3), and (4) of Article 66 and Article 54 of Law No. 30 of 2004 concerning Notary Position which requires the notary to keep the contents of the deed made from another party if the other party does not have a strong legal basis to request that the notary notify the contents of the deed made by the notary.Keywords: Right, Obligation, Notary’s Objection